2023
DOI: 10.3390/en16041663
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Characterization of Pore Structure Parameters in Coal Based on Image Processing and SEM Technology

Abstract: The pore structure parameters of coal have an important influence on the exploration and development of coalbed methane. In this study, a series of pore structure parameters, including porosity, pore radius, pore throat radius, pore coordination number, pore throat ratio, and specific surface area, are identified, extracted, and calculated in the scanning electron microscopy (SEM) images of coal reservoir samples using algorithms and application programs in MATLAB. Constant rate-controlled mercury injection an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Most of the existing studies on low-temperature fracturing of coal bodies by liquid nitrogen have investigated the freezing time and cyclic freezing of coal bodies by liquid nitrogen, i.e., they mainly focus on the "freezing" aspect, but few studies have investigated the ablation time of coal bodies after freezing by liquid nitrogen, i.e., they lack the "melting" aspect [31][32][33][34][35][36][37][38][39][40][41]. Jia Peng [42] tested the elastic modulus and hardness of coal samples frozen by liquid nitrogen using the nanoindentation technique and concluded that the elastic modulus and hardness of coal samples increased after freezing by liquid nitrogen. Peng concluded that the reason was that the water in the pores and fissures of coal samples changed from liquid to solid after freezing, which supported the pores and fissures and thus increased the hardness.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the existing studies on low-temperature fracturing of coal bodies by liquid nitrogen have investigated the freezing time and cyclic freezing of coal bodies by liquid nitrogen, i.e., they mainly focus on the "freezing" aspect, but few studies have investigated the ablation time of coal bodies after freezing by liquid nitrogen, i.e., they lack the "melting" aspect [31][32][33][34][35][36][37][38][39][40][41]. Jia Peng [42] tested the elastic modulus and hardness of coal samples frozen by liquid nitrogen using the nanoindentation technique and concluded that the elastic modulus and hardness of coal samples increased after freezing by liquid nitrogen. Peng concluded that the reason was that the water in the pores and fissures of coal samples changed from liquid to solid after freezing, which supported the pores and fissures and thus increased the hardness.…”
Section: Discussionmentioning
confidence: 99%
“…Leveraging the capabilities of the Python programming language, the methodology proposed by [52] is implemented for noise reduction and segmentation, employing the Multi-Scale Retinex with Color Preservation and Color Image Quantization method on the BH I log. Following segmentation, the determination of pore size is conducted by adopting the porous radius representation outlined by [53]. The final size value is defined as the average of major and minor axes, calculated through the opencv library function, "boundingRect()", which provides values for the major and minor axes of a convex contour (such as porous).…”
Section: Image Segmentation For Pore Size Classificationmentioning
confidence: 99%